Ability of aphasic individuals to perform numerical processing and calculation tasks - Gabriela De Luccia (Arquivos de Neuro-Psiquiatria, 2014)
Objective To compare performance on EC301 battery calculation task between aphasic subjects and normal controls of the same sex, age, and education. Method Thirty-two aphasic patients who had suffered a single left hemisphere stroke were evaluated. Forty-four healthy volunteers were also selected. All subjects underwent a comprehensive arithmetic battery to assess their numerical and calculation skills. Performances on numerical processing and calculation tasks were then analyzed. Results Aphasic individuals showed changes in their ability to perform numerical processing and calculation tasks that were not observed in the healthy population. Conclusion Compared with healthy subjects of the same age and education level, individuals with aphasia had difficulty performing various tasks that involved numerical processing and calculation.